Kajian penilaian faktor yang menyumbang kepada kepuasan bekerja dalam kalangan staf Jabatan Perbendaharaan Negeri Kedah Darul Aman - Sharifah Noriza, Syed Mohamad (2013)
The purpose of this study was to identify the factors that influence job satisfaction among staff of the Treasury Department of Kedah. The scope of the study involves four (4) factors, factor payments, and administrative leadership factors, contingent reward factor and factor support colleagues. The study involved 60 staff from the Treasury Department of Kedah. The instrument used was a questionnaire that is divided into six (6) of section A to see the background of the respondents and the B, C, D, E, F and G are to see the feedback survey respondents on the statement. The data were analyzed using SPSS perisian. Data were analyzed in terms of frequency, percentage, mean, standard setting deviation, factor analysis and correlation factors. The results showed that all four factors, payment, and administrative leadership, reward and support colleagues kontinjen significantly correlated with job satisfaction